1994
DOI: 10.1902/jop.1994.65.4.350
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Repair in Dogs: Space Provision by Reinforced ePTFE Membranes Enhances Bone and Cementum Regeneration in Large Supraalveolar Defects

Abstract: Regeneration of alveolar bone and cementum following reconstructive therapy with reinforced space providing expanded polytetrafluorethylene (ePTFE) membranes was evaluated in supraalveolar mandibular premolar periodontal defects in five beagle dogs. The surgically-created defects in contralateral jaw quadrants were randomly assigned to receive the dome-shaped membrane or serve as surgical control. Flaps were positioned to completely submerge the teeth and sutured. The dogs were sacrificed 8 weeks after surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
124
2
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 16 publications
18
124
2
3
Order By: Relevance
“…2,3 Studies have also shown that alveolar bone and cementum regeneration is critically dependent on space provision by the GTR device. [4][5][6][7][8][9] With limited space provision by the barrier membrane, alveolar bone will fill the space provided by the device. 4,9 In presence of a larger space, the alveolar bone adopts a physiologic form along the entire root surface, the remainder of the space being filled by fibrous connective tissue.…”
Section: G Uided Tissue Regeneration (Gtr) Ismentioning
confidence: 99%
See 3 more Smart Citations
“…2,3 Studies have also shown that alveolar bone and cementum regeneration is critically dependent on space provision by the GTR device. [4][5][6][7][8][9] With limited space provision by the barrier membrane, alveolar bone will fill the space provided by the device. 4,9 In presence of a larger space, the alveolar bone adopts a physiologic form along the entire root surface, the remainder of the space being filled by fibrous connective tissue.…”
Section: G Uided Tissue Regeneration (Gtr) Ismentioning
confidence: 99%
“…4,9 In presence of a larger space, the alveolar bone adopts a physiologic form along the entire root surface, the remainder of the space being filled by fibrous connective tissue. 5,6,8,9 Collapse or compression of the barrier device into a periodontal defect or onto the root surface will necessarily compromise regeneration of alveolar bone and cementum following GTR procedures. [4][5][6][7][8][9] The space provided by the device at the time of surgery is lost and the device becomes a physical obstacle to bone and cementum regeneration.…”
Section: G Uided Tissue Regeneration (Gtr) Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Many years before, the key role of space provision and wound stability in regenerative treatment was reported by some studies evaluating the guided tissue regeneration techniques and as verified, possibility of bone formation increases by providing space provision without rigorous interruption of the gingival connective tissue [21,24,25]. PRF was covered over the defect as a membrane in the first surgical step of the present case, and the role that was imputed to the PRF membrane was containing the infrabony part of the defect in the early phase of healing due to this principle.…”
Section: Discussionmentioning
confidence: 94%